Obtaining forest foods from timber trees in Cameroon: How far do people walk to collect fruits and caterpillars? - Maukonen, P.; Donn, P.; Snook, Laura K.; Bioversity International (2014)
Approximately 61% of timber species in the Congo Basin also bear locally used non-timber forest products. Amongst these are fruits of Baillonella toxisperma, and edible caterpillars on Entandrophragma cylindricum and Erythrophleum suaveolens. Participatory mapping combining GPS coordinates and interviews was carried out with collectors in villages adjacent to logging concessions in Cameroon in order to: locate the trees from which men and women obtained these foods; determine the distances travelled by men and women to collect these wild resources; and assess the potential impacts of logging activities on local people’s access to these food resources